PENGEMBANGAN APLIKASI SISTEM INFORMASI PRAKERIN BERBASIS ANDROID DI JURUSAN ELEKTRONIKA INDUSTRI SMKN 1 CIKANDE - Muhammad Amir Baihaqi; Didik Aribowo; Mustofa Abi Hamid (JPTE FT UNY, 2020)
ABSTRACTThis study aims to produce a product in the form of an Android-based apprenticeship information system in the Department of Electronics Industry, Vocational Secondary School (SMK) Negeri 1 Cikande. The development model used is a Waterfall with a software development method that has four stages: (1) Systems Analysis, (2) Design, (3) Programming, and (4) Testing. The test subjects consisted of 2 teachers and 24 students with data collection techniques in the form of literature and questionnaire studies. Media expert data collection has two aspects, namely: visual appearance and communication, while the user contains three points, including accuracy, visual communication, and data input. The results of user trial through questionnaires distributed to teachers obtained a value of 78.7% and students at 79.86% can be declared feasible. The implication of the results of this study is an Android application that is used by teachers, supervisors, and students for industrial work activities in the Department of Electronics Industry, SMK Negeri 1 Cikande, to make it faster, easier, and more efficient in conducting the internship process.Keywords: Implications, Research and Development, Trial Results, Waterfall.ABSTRAKPenelitian ini bertujuan menghasilkan produk berupa sistem informasi prakerin berbasis Android di Jurusan Elektronika Industri SMK Negeri 1 Cikande. Model pengembangan yang digunakan ialah Waterfall dengan metode pengembangan software yang memiliki empat tahapan: (1) Analisis Sistem, (2) Desain, (3) Pemrograman, dan (4) Uji coba. Subjek uji coba berjumlah 2 guru beserta 24 siswa dengan teknik pengumpulan data berupa studi pustaka dan kuisioner. Pengumpulan data ahli media memiliki dua aspek yaitu tampilan dan komunikasi visual, sedangkan pengguna berisi tiga aspek diantaranya akurasi, komunikasi visual, dan penginputan data. Hasil ujicoba pengguna melalui kuesioner yang disebarkan kepada guru memperoleh nilai sebesar 78,7% dan siswa sebesar 79,86% sehingga dapat dinyatakan layak. Implikasi dari hasil penelitian ini ialah sebuah aplikasi Android yang dimanfaatkan oleh guru, pembimbing, dan siswa untuk kegiatan prakerin di Jurusan Elektronika Industri SMK Negeri 1 Cikande, agar lebih cepat, mudah, dan efisien dalam melakukan proses prakerin.